2019
DOI: 10.15406/ijmboa.2019.04.00123
|View full text |Cite
|
Sign up to set email alerts
|

Pathological characterization of lesions and bacteriological isolation of causative agents of swine tuberculosis at Bishoftu and Addis Ababa Abattoirs, Bishoftu, Ethiopia

Abstract: Pathological characterization of lesions and bacteriological isolation of causative agents of swine tuberculosis at Bishoftu and Addis Ababa Abattoirs,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Before this study there were no reported prevalence of swine tuberculosis in Ethiopia and they were designed to estimate the prevalence of TB in pigs in central Ethiopia and characterized the causative agents [11]. Shiferaw et al [26]. reported, 19.6% (109/556) prevalence of swine tuberculosis, out of five hundred and fifty six (556) swine examined, tubercle like granulomatous lesion were detected in different organs.…”
Section: Prevalence Of Swine Tuberculosis In Ethiopianmentioning
confidence: 99%
“…Before this study there were no reported prevalence of swine tuberculosis in Ethiopia and they were designed to estimate the prevalence of TB in pigs in central Ethiopia and characterized the causative agents [11]. Shiferaw et al [26]. reported, 19.6% (109/556) prevalence of swine tuberculosis, out of five hundred and fifty six (556) swine examined, tubercle like granulomatous lesion were detected in different organs.…”
Section: Prevalence Of Swine Tuberculosis In Ethiopianmentioning
confidence: 99%